An extended expectation confirmation model of continuance intention to use online food delivery services in Asia country - Lim, Xhi Bo; Lee, Angela Siew Hoong * (2021)
E-commerce is a well-known term in this 21st century, moved from being a trend to be an anchor reality that numbers of adoption increases months after months. Most shopper nowadays prefer e-commerce platforms as a shopping medium because they can purchase all kinds of products at the comfort of their own home anytime, anywhere as long as there is internet connection and they are financially stable. E-commerce is practically in every field of industry – fashion, banking, social, travel and more have grew with absurd speed, gaining soar importance among the population in the world. E-commerce means an extensive choice of products and services that provide the shopper with real time interactive communication, product customization and prompt delivery. These data indicate that information technology and communication (ICT) is experiencing speedy growth in Malaysia. When more people are using the internet in turn the power of e-commerce are growing exponentially too. Online Food Delivery System (OFDS) can be categorized as part of e-commerce but due to lack of study in this topic and the recent rise of commercializing OFDS, it is vital to be keep up with the trend of e-commerce and study exclusively on OFDS particularly in Asia country. This study proposed a conceptual model where it integrates constructs such as perceived value such as money, performance, social, emotional during COVID pandemic and trust in influencing the consumer continuance intention to use online food delivery system.